FACTORS RELATED TO PAIN RESPONSE IN INPATIENTS AT RSUD EMBUNG FATIMAH - Muharni , Sri; Christya Wardhani, Utari; Hanjani, Riska (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Objective: Pain is a sensory and emotional experience that will cause a response in the body. It was found that on average inpatients at Embung Fatimah Regional Hospital received a nursing diagnosis of pain. This research was conducted to determine the factors associated with pain responses in inpatients at Embung Fatimah Regional Hospital. The factors that will be studied are age, gender, anxiety and coping mechanisms. The instruments in this research are a questionnaire and pain measurement using a numerical rating scale. Methods: A quantitative cross-sectional study was conducted on 110 inpatient using accidental sampling technique. Data wereanalyzed using chi-square tests to test Factors that are related to pain responses in inpatients are Gender, Anxiety and Coping Mechanisms, while those that are not related are Age Results: The results of this study indicate that the factors associated with pain response in inpatients at Embung FatimahGeneral Hospital are gender (p value = 0.003), anxiety (p value = 0.011), coping mechanisms (p value 0.017) and factor that is not related to the pain response in inpatients at Embung Fatimah Regional Hospital is age with a value (p value = 0.196). Conclusion: Factors that are related to pain responses in inpatients at Embung Fatimah Regional Hospital are Gender, Anxiety and Coping Mechanisms, while those that are not related are Age. In this study there were more women (65 people) while only men (45 people).